Human leucocyte antigen class I in hormone receptor-positive, HER2-negative breast cancer: association with response and survival after neoadjuvant chemotherapy - Sinn, Bruno; Weber, Karsten E.; Schmitt, Wolfgang Daniel; Fasching, Peter Andreas; Symmans, William Fraser; Blohmer, Jens-Uwe; Karn, Thomas; Taube, Eliane Tabea; Klauschen, Frederick; Marmé, Frederik; Schem, Christian; Stickeler, Elmar; et al. (Breast cancer research, 2019)
Clinical application of cancer immunotherapy requires a better understanding of tumor immunogenicity and the tumor microenvironment. HLA class I molecules present antigens to CD8+ cytotoxic cells. Their loss or downregulation is frequently found in tumors resulting in reduced T cell responses and worse prognosis.